Metode ST-Disprescreat Untuk Meningkatkan Kemampuan Siswa Menangkap Makna Kata Kontekstual Lagu Bahasa Inggris - Khoirulhadi, Muhammad (FKIP Universitas Muhammadiyah Sukabumi, 2018)
The objective of this research improves the students’ competency in catching the contextualmeaning and analyzes language features of English song lyrics by implementing ST-DISPRESCREAT(Singing, Thinking, Presenting, Creating) Method in Class 11 IPA3 at SMAN 4 Sukabumi. The classconsists of 16 male students and 25 female students. The procedures of this research are planning, action,observation and reflection. This Classroom Action Research is about implementing the STDISPRESCREATMethod. This research is carried out in two cycles and each cycle in two actions. Thisresearch can be concluded as follows: 1) the teacher could be improved the students’ competency incatching the contextual meaning and analyzing language features of English song lyrics in Class 11 IPA3at SMAN 4 Sukabumi well; 2) it can be proved that there is the improvement the students’ competency incatching the contextual meaning and analyzing language features of English song lyrics. The datarevealed that the rate achievement of the students’ pre-test was 67 then became 76 in the first cycle and80 in the second cycle. The percentage of the minimum criteria of mastery students’ competency was 51%in pre-test, 73% in first cycle and 93% in the second cycle. 3) there were the improvement percentage ofthe students’ enthusiasm 87% in the first cycle then became 92% in the second cycle.